Application of Non-destructive Testing in Quality Control of Manufactured Aluminium Metal Matrix Composite Components for the Automotive Industry - C. Sofia Proença; Paulo Morais; F. Salgueiro; Beatriz Correia; Ana Beatriz Lopez; C. Kneissl; T. Petkov (Research and Review Journal of Nondestructive Testing, 2023)
The manufacturing of automotive components using aluminium metal matrix composites (Al-MMCs) is progressively gaining a relevant place in the automotive industry. Due to the increasing competition in the automobile sector, there is a great need to supply efficient, stable, and high-quality products. Generally, following automotive standards is voluntary, which means that businesses and other organizations are not legally obliged to apply them. Nevertheless, in certain cases standards may facilitate compliance with legal requirements, such as those contained in European directives and regulations. IATF 16949:2016 is the current version of the IATF 16949 Standard and outlines the requirements an organization must maintain in their quality system for IATF 16949 certification. This new application of manufacturing Al-MMCs requires additional procedures to guarantee the quality of the components manufactured. Because the manufacturing process may generate various defects, such as cracks, voids, lack of fusion, inclusions, porosities, and other metallurgical aspects, non-destructive testing (NDT) techniques should be used for guaranteeing the quality of the components manufactured. The development of reliable NDT methods for aluminium metal matrix composite parts is thus a major challenge. This aspect is related to how NDT procedures need to be optimised or developed to address the singular structures of the processes, such as complex geometry, anisotropic material properties, special internal structures, and the presence of nanoparticles. The main objective of this work is to summarize and present the relevant potential of different NDT techniques used in quality control of manufactured Al-MMC components in the automotive industry, to be explorer in the European FLAMINGo project (Fabrication of Lightweight Aluminium Metal Matrix Composites and Validation in Green Vehicles). This study is very significant because the NDT techniques present different probabilities of detection of the defects, principally of the microdefects.